PWE-235 Long term subcutaneous saline and magnesium administration in patients with a short bowel. 10 year outcomes. (22nd June 2015) - Small, M; Brundrett, D; Nightingale, JM
Abstract : Introduction: Subcutaneous administration of water, sodium and magnesium is a treatment for patients with a short bowel and an adequate nutritional status, but with sodium and magnesium depletion. This study aimed to determine the long-term outcomes of patients treated with subcutaneous fluid (SCF). Method: 10 year retrospective review of medical, dietetic and pharmacy records of patients identified as receiving home SCF administration from an 'Intestinal Failure' database. All patients selected had had an inpatient assessment in which bowel function was optimised and a subcutaneous regimen established. All patients were taught to self-administer fluids via gravity through a 22 Gauge plastic cannula inserted prior to each infusion into the subcutaneous tissue of the upper leg or abdomen. Patients were reviewed 3–6 monthly. Results: 26 patients (19F:7M) were identified). Mean BMI 23.1 ± 4.7 (18.1–41.4). Mean time receiving SCF was 22 ± 34 (0.5–139) months. Underlying condition was Crohn–s/ulcerative colitis (n = 10), surgical complications (n = 8), mesenteric infarction (n = 5), other (n = 3). Mean infusion volume was 4 ± 2.1 (0.5–7) litre/week. 4(15%) patients had <100cm small bowel to stoma, mean duration of SCF was 11 ± 6.9 (3–18) months. 9 (35%) patients had 100–150cm small bowel to stoma, mean duration 16 ± 23 (2–74) months. 11(42%) patients had more than 150cm small bowel to stoma, mean duration 32 ± 47 (0.5–139) months. 2(8%) patients had small bowel to colon, mean duration 19.5 ± 2.1 (18–21) months. There was no difference between patients with <150cm small bowel vs those with >150cm, p = 0.25. 21(81%) patients had magnesium in their infusions, mean 21 ± 9.8 (8–40) mmol per week; 16(76%) having 4mmol and 5(24%) having 8mmol per infusion. Patients on 4mmol magnesium were on treatment 17.4 ± 34 (3–139) months, those on 8mmol 10 ± 8.5 (2–24) months. The difference between these was not significant p = 0.4. Most patients 20(77%) had no complications. 5(19%) patients had leaking at the infusion site after a mean time of 50 ± 56 (8–139) months. Failure of treatment was most commonly due to an infusion taking too long to go in (more than 14 h ± fluid leaking (n = 6). In 2 patients the treatment did not correct magnesium, 2 patients had weight loss requiring parenteral nutrition. 6 patients stopped after corrective surgery. 2 patients were transferred elsewhere. 8 patients are still on treatment. Conclusion: SCF are well tolerated in patients with a short bowel and sodium and magnesium depletion. Most patients continue with no complications for more than a year. Stopping SCF did not relate to small bowel length or the presence of magnesium but most commonly to the failure of the subcutaneous tissues to accept the infusion fluid. Disclosure of interest: None Declared.